The rituals and myths of the feast of the goodly gods of KTU/CAT 1.23: royal constructions of opposition, intersection, integration, and domination - Smith, Mark S. (Resources for biblical study, 2006)
Text of the work known as The birth of the beautiful gods, in parallel columns: Ugaritic (romanized) and English (p. 18-25), with commentary and discussion in English